Cognitive Risk Framework for Cybersecurity: Bounded Rationality: Executive Summary: Part I. Issue 5 (1st November 2016) - Bone, James
Abstract: Cyber risk professionals face a formidable challenge in keeping pace with the asymmetric nature of today's advanced threats in cyber security. Spending on cyber security has skyrocketed yet the threat continues to grow exponentially. This phenomenon is called the Cyber Paradox and describes what has become an entrenched battle for security professionals in defending against an increasingly sophisticated adversary that, to date, has adapted faster than defensive measures to prevent loss of data or access to sensitive information. Conventional security defenses have proven less than effective resulting in a virtual "Maginot's Line" of increased fortification by hardening the enterprise yet resulting in greater vulnerability to achieving the goals of defending the organization from cyber threats ("Maginot's Line", n.d.). This article reviews the causes of these misperceptions in security defense and explores research in decision science, intelligence and security informatics, machine learning, and the role of simplicity in shaping a cognitive risk framework. The findings conclude that the human-machine interaction is the greatest threat in cyber space yet very few, if any, security professionals are well versed in strategies to close this gap. The purpose of this article is to bring to light evolving new strategies with promising success and to reveal a few surprises in how simplicity is an under-appreciated strategy in cyber security. Complete text of "Cognitive Hack: The New Battleground in Cybersecurity … the Human Mind" is available here:https://www.crcpress.com/Cognitive-Hack-The-New-Battleground-in-Cybersecurity–the-Human-Mind/Bone/p/book/9781498749817